Positive solutions for nonlinear elastic beam models - Bendong Lou (International Journal of Mathematics and Mathematical Sciences)
We give a negative answer to a conjecture of Korman on nonlinear elastic beam models. Moreover, by modifying the main conditions in the conjecture (generalizing the original ones at some points), we get positive results, that is, we obtain the existence of positive solutions for the models.